Cultural and heritage tourism and management - Kaufman, Tammie J. 1969- (Tourism and hospitality management collection, 2018)
1. Introduction to cultural and heritage tourism -- 2. Cultural and heritage tourism resources -- 3. Cultural and heritage tourism planning and development -- 4. Cultural and heritage tourism impacts: creating a sustainable experience -- 5. Marketing cultural and heritage tourism -- 6. The role of festivals in cultural and heritage tourism -- 7. Rural tourism development and the interdependence with cultural and heritage tourism -- 8. Addressing darker cultural and heritage attractions -- 9. Cultural and heritage tourism trends -- About the author -- Index